Process analysis and material behavior of thermoplastic elastomers throughout the laser sintering processing chain - Ziegelmeier, Stefan (2016)
Laser sintering (LS), an additive manufacturing (AM) technology, allows for the production of 3-dimensional parts by fusing together successive layers of polymer powder without the need for tooling. Its potential and applicability, however, is still constrained due to the limited repertoire of materials available and the lack of detail in understanding both the important process-material interactions and consequently the requirements for the development of new materials. Past research has mainly focused on polyamide 12 (PA12) as the standard material, hence most of the empirically grown or theoretical, often idealized, process models are based on this polymer. As a result, it was shown that there are strong interactions between the material and the process leading to an undesired deviation of part properties. Thermoplastic elastomers (TPEs) for LS have gained more and more popularity for the production of, for example flexible parts in the recent past but they are a group of polymers that is neither well studied nor understood regarding their use in LS. Therefore, this PhD investigation has focused on TPEs in order to reveal their process specifics throughout the processing chain in LS.